Voters’ Preferences: Possible considerations electing representative for development in constituency / Glenn Achang Henry ... [et al.] - Henry, Glenn Achang; Adenan, Abdul Muzhaffar; Augustine, Elizabeth Caroline; Kipli, Nur Aida (2021)
The development of a constituency relies on a representative elected in an election. The purpose of this paper is to highlight the possible considerations used by voters to elect their representatives to foster development in their constituencies. This paper was written based on an analysis of literature significantly related to voters' preferences in electing their representatives. This paper also attempts to find out the characteristics of representatives that might have influence voters' preferences to elect them. It also seeks to figure out if the attribute of representatives elected contributed to the development in the constituencies. The findings led to suggestions for the qualities that a representative should possess to bring major changes to the constituency that he or she is representing, as well as the types of changes that voters want to see in their area in the future. It is hoped that representatives can bring sustainable development within the communities and in the constituencies. This is consistent and following United Nations Sustainable Development Goals (UN SDGs).